Karakteristik dan Tipologi Perubahan dI Kawasan Pusat Kota Semarang - Handayani, Wiwandari; Mardiansjah, Fadjar Hari; Febriyanto, Ahady Farrel (Badan Riset dan Inovasi Daerah Kota Semarang, 2023)
The city center's decline is a severe problem faced by cities worldwide and the City of Semarang. The population decline has coincided with the transformation of urban villages in the Central Region of Semarang City. Many dwellings have changed their function due to the growth in commercial activity, which then affected the physical form of settlements in the area. Therefore, the city center often experiences depreciation and creates vacant land, which also impacts ongoing environmental degradation. The physical transformation of urban villages needs to be identified as a positive opportunity to develop a more productive city center. This study aims to identify the characteristics and typologies in the city center to model the development of the Semarang City Center Area. This study uses a mixed research methods approach (mixed method) and used primary data in questionnaires distributed to the community in the Central City of Semarang. Respondents in this study are people who live in two residential groups, namely Kampung Kota (Urban Villages) and Planned Housing. The result is that there are four typologies based on settlement characteristics and changes in their function. These typologies include Fixed Planned Housing, Changed Planned Housing, Fixed Urban Villages and Changed Urban Villages. Then the four typologies become the basis for the development model of the Semarang City Center Area, looking at the opportunities and challenges.